KAJIAN KOMPOSISI SERANGGA POLINATOR PADA TUMBUHAN PENUTUP TANAH DI PONCOKUSUMO – MALANG - Budi Purwantiningsih; Amin Setyo Leksono; Bagyo Yanuwiadi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2012)
The use of pesticides on agricultural land has a negative impact on health, economic, and environment. The using of variety of ground cover plants as refugia area are expected to be an alternative habitat for pollinators insect in plants: Cyperus rotundus L., Bidens pilosa L., Commelina difussa L., Capsicum frutescens L., and Ageratum conyzoides L. Observations made by "visual control". This reseacch aims to know the composition of pollinators insect visit of ground cover plants and analyze their patterns. Analysis of the data structure of insect communities in the spring and the fruit season obtained from INP and diversity (Shannon-Winner Index). Parameters are compared to diversity and abundance with ANOVA test, composition using Morisita Index. The results show that the abundance of insect pollinators of spring higher at 7 families (31%) with H '= 1.698 instead of the fruit season is 6 families (25%) with H' = 1.600. Abundance and diversity of pollinators insect in the spring and fruit season with a significance of P < 0.05. Morisita similarity index of 82%. Analysis of environmental factors of temperature, humidity, and light intensity on the abundance of insect pollinators found positive correlation with R-square 87.5%.